2020
DOI: 10.1371/journal.pone.0235437
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Acute Respiratory Distress Syndrome (ARDS) in adults with imported severe Plasmodium falciparum malaria: A 10 year-study in a Portuguese tertiary care hospital

Abstract: Background Acute respiratory distress syndrome (ARDS) is a severe complication of malaria that remains largely unstudied. We aim to describe the development of ARDS associated with severe P. falciparum malaria, its management and impact on clinical outcome. Methods Retrospective observational study of adult patients admitted with severe P. falciparum malaria in an Intensive Care Unit (ICU) of a tertiary care hospital from Portugal from 2008 to 2018. A multivariate logistic regression analysis was used to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This enables clinicians to prompt appropriate countermeasures at the earliest possible stage such as oxygen supplementation, application of positive airway pressures, fluid restriction, diuretics, or, if indicated, mechanical ventilation. In the present study, nearly half of patients with respiratory failure had successfully been treated with non-invasive ventilation (NIV), which is an option for eligible patients with APO and mild forms of ARDS [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This enables clinicians to prompt appropriate countermeasures at the earliest possible stage such as oxygen supplementation, application of positive airway pressures, fluid restriction, diuretics, or, if indicated, mechanical ventilation. In the present study, nearly half of patients with respiratory failure had successfully been treated with non-invasive ventilation (NIV), which is an option for eligible patients with APO and mild forms of ARDS [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Portugal, there is a clear need for a systematic and more efficient method of early diagnosis, monitoring and referral of malaria cases to an appropriate health facility, not only to reduce probability of reintroduction [95] but to prevent severe disease and death. Recently, two studies involving 59 and 98 patients reported case fatality of 15.2% [14] and 4.1% [96], respectively. Malaria is a curable disease.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical deterioration usually appears 3-7 days after onset of fever [1,4,25]. Complications involve the nervous, respiratory, renal, and/or hematopoietic systems like malignant anemia [5][6][7][8][9][10][16][17]25], Metabolic acidosis [26] and hypoglycemia [27] are also common systemic complications.…”
Section: Clinical Spectrum Of Severe Malariamentioning
confidence: 99%
“…Severe malaria arises when the course of the disease are complicated by serious organ failures which can occur simultaneously or fatal abberations in the patient's blood component or in his/her metabolism followed with the loss of consciousness and coma leading to death [1][2][3]. The various manifestations of severe malaria include the following: pulmonary derangement marked by severe respiratory distress [5], acute renal failure [6], cerebral malaria with abnormal behavior [7], impairment of consciousness [8], seizures [9], coma [10], or other neurologic abnormalities [4,5]. The disturbed diversity of internal organs shows how vulnerable and interrelated these organs are and their main blood supply is supported by a network of capillaries and how microcirculatory obstruction in malaria directly affect the function of these organs [11].…”
Section: Introductionmentioning
confidence: 99%